The effectiveness of integrating ICTs in the teaching of Mechanical System and control in a Grade 8 Technology subject: a case of two township schools. - Nkosi, Nobuhle (My University, 2020)
Information and Communication Technology (ICT) in the education system have been highly received and thus viewed as a catalyst for change in teaching and learning practise that take place in the classroom. ICTs have been highly researched in the education systems globally and their impact in education has been phenomenal at most. This is because ICTs are introduced in schools as a means of improving educational outcomes with hope to also enhance the standard of teaching and learning. Within the education system, the assumptions is that “ICT helps in providing a catalyst for rethinking teaching practices” (Flecknoe, 2002; McCormick & Scrimshaw, 2001 cited in Noor-Ul-Amin, 2013, p.8). The research aimed at investigating how effective teaching and learning was achieved using ICTs in the subject Technology classroom, especially in teaching of a Mini-PAT in the concept of Mechanical Systems and Control. This research explored skills and competencies needed by teacher to help them integrate ICTs into their lessons and teaching and the challenges they face. The study explored how effective teaching and learning was achieved by Grade 8 Technology teachers when ICTs were integrated into their lessons, especially in the teaching of a Mini PAT in the concept of Mechanical system and control. Mishra and Koehler (2013) technology, pedagogy, and content knowledge (TPACK) were used to frame the research. This research employed a qualitative research approach. Purposive sampling was used to select four secondary school teachers who teach Technology Grade 8. Semi- structured interviews and classroom observation were used as a means of collecting data. The research findings revealed that teacher’s attitude, perceptions and beliefs shape the manner in which ICTs are integrated and utilised within the subject hence its effectiveness in practice. The study also found that policy regarding ICTs is not made transparent to teachers and stakeholders. The study concluded that the TPACK of the participants influenced and shaped effective teaching and learning practices when ICTs were integrated into their lessons, especial in the teaching of the concept of Mechanical systems and control and its Mini PAT. The study recommended; providing teacher professional development centres whereby teacher can learn to develop activities related to technology as means of enhancing their technology skills, providing teachers support partnership that can enable them to share effective strategies for technology, matching the content uploaded onto the smartboard with the teachers’ set work, school’s curriculum policy and textbooks, having a technical support team that is well trained and available at schools at all times, decentralising the technical assistance and training to name but a few. Furthermore, the schools policy must be adjusted to fit ICT rules usage in class and school, to enable the teacher to use effectively ICT tools and be able to manage their classrooms and teaching using ICTs.
A thesis submitted in partial fulfilment of the requirements for the Degree of Master of Education to the Faculty of Humanities, Wits School of Education, University of the Witwatersrand, Johannesburg, 2019
Keywords: Educational technology; Technology-Study and teaching-South Africa